2019
DOI: 10.1515/nanoph-2019-0310
|View full text |Cite
|
Sign up to set email alerts
|

All-in-one silicon photonic polarization processor

Abstract: With the great developments in optical communication technology and large-scale optical integration technology, it is imperative to realize the traditional functions of polarization processing on an integration platform. Most of the existing polarization devices, such as polarization multiplexers/demultiplexers, polarization controllers, polarization analyzers, etc., perform only a single function. Definitely, integrating all these polarization functions on a chip will increase function flexibility and integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…For industrial production integrating the lasing source with the sensor has the advantages of cutting on the cost and eliminating the intensity fluctuation of the input light due to vibrations in the coupling fiber. The integration of a programmable polarization controller [47,48] on the sensor chip to couple the desired fundamental mode is also advantageous to avoid the cost of expensive external polarization controllers. The different photonic components on the integration template of the sensor are connected by waveguides.…”
Section: The Principle Of Operation and Detection Systemmentioning
confidence: 99%
“…For industrial production integrating the lasing source with the sensor has the advantages of cutting on the cost and eliminating the intensity fluctuation of the input light due to vibrations in the coupling fiber. The integration of a programmable polarization controller [47,48] on the sensor chip to couple the desired fundamental mode is also advantageous to avoid the cost of expensive external polarization controllers. The different photonic components on the integration template of the sensor are connected by waveguides.…”
Section: The Principle Of Operation and Detection Systemmentioning
confidence: 99%
“…The spike temporal encoding, excitatory and inhibitory response, refractory period, and spike-timing dependent plasticity (STDP) have been demonstrated numerically and experimentally. From the architectures and algorithm perspective, different architectures, such as optical matrix computation [184,185], photonic inmemory computing [186], photonic convolutional neural network [187,188], photonic reservoir computing [189,190], and photonic SNN [191,192], have been explored in recent years.…”
Section: Photonic Neuromorphic Computing Chips: From Devices To Integrated Circuitsmentioning
confidence: 99%
“…The following year, Hughes et al thoroughly discussed the training of ONNs by backpropagation and gradient measurement [ 52 ], and this work provided a path toward effectively implementing on-chip training and optimizing reconfigurable integrated optical platforms. By applying on-chip training on the integrated optical platform, Zhou et al proposed and experimentally demonstrated an all-in-one silicon photonic polarization processor [ 53 , 54 ], a universal matrix computing chip [ 55 ], and a self-configuring programmable signal processor [ 56 ], etc. Beyond the applications in machine learning, these works may also broaden the access to intelligent optical information processing.…”
Section: Mzi Matrix Corementioning
confidence: 99%